Proceedings of the International Conference on Management, Accounting, and Economy (ICMAE 2020) 2020
DOI: 10.2991/aebmr.k.200915.002
|View full text |Cite
|
Sign up to set email alerts
|

The Gender Effect on Banking Performance in Indonesia

Abstract: This paper aims to study the determinants of banking performance from human equality perspective. Banking is a service industry which heavily depends on the human resources. Therefore, the research will focus on the diversity of employees and board member in determining the financial performance. We have analysed 2 ratios which are the gender diversity of total employees and gender diversity in board members. The dependent variable is Return on Asset (ROA). We use linear regression. The samples are 11 banks wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…This relationship was previously investigated by Johan and Hapsari (2020); Handa (2018); Kramaric and Pervan (2016); Belhaj and Mateus (2016); Kilic (2015); Fidanoski et al (2014); Liang et al (2013); Pathan and Faff (2013); Bonn et al (2004). However, only Johan and Hapsari (2020), Kilic (2015) and Fidanoski et al (2014) showed significance in the studies, which accompany the findings of this research.…”
Section: Source: Authorssupporting
confidence: 55%
See 2 more Smart Citations
“…This relationship was previously investigated by Johan and Hapsari (2020); Handa (2018); Kramaric and Pervan (2016); Belhaj and Mateus (2016); Kilic (2015); Fidanoski et al (2014); Liang et al (2013); Pathan and Faff (2013); Bonn et al (2004). However, only Johan and Hapsari (2020), Kilic (2015) and Fidanoski et al (2014) showed significance in the studies, which accompany the findings of this research.…”
Section: Source: Authorssupporting
confidence: 55%
“…Aslam and Haron (2020);Gyamerah et al (2020);Johan and Hapsari (2020);Haris et al (2019);Aktan et al (2018);AlSagr et al (2018);Hajer and Anis (2018);Chou and Buchdadi (2017);Isik and Ince (2016);Belhaj and Mateus (2016);Bukair and Rahman (2015);Boussaada and Karmani (2015);Kilic (2015);Fidanoski et al (2014);Chaarani (2014);Abdul et al (2014);Liang et al (2013);Pathan and Faff (2013);Adams and Mehran (2012);Andres and Vallelado (2008);Adams and Mehran (2008);Bonn et al (2004).ROEMeasures the profitability of the company's shareholders 'equity, defined by the ratio between Net Income and Shareholders' Equity Aslam and Haron (2020)Haris et al (2019);Aktan et al (2018);Handa (2018);AlSagr et al (2018);Hajer and Anis (2018);Kramaric and Pervan (2016);Belhaj and Mateus (2016);Bukair and Rahman (2015);Boussaada and Karmani (2015);Kilic (2015); Chaarani (2014); Fidanoski et al (2014); Liang et al (2013); Pathan and Faff (2013(2020); Gyamerah et al (2020); Haris et al (2019); Aktan et al (2018); Handa (2018); AlSagr et al (2018); Hajer and Anis (2018); Chou and Buchdadi (2017); Kramaric and Pervan (2016); Isik and Ince (2016); Belhaj and Mateus (2016); Bukair and Rahman (2015); Boussaada and Karmani (2015); Kilic (2015); Chaarani (2014); Fidanoski et al (2014); Abdul et al (2014); Liang et al (2013); Pathan and Faff (2013); Adams and Mehran (2012); Andres and Vallelado (2008); Adams and Mehran (2008); Bonn et al (2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suciu, Noja, and Cristea (2020) highlighted the value of social inclusion, professional and personal growth, and gender and cultural diversity in reducing risks faced by European businesses and enhancing profitability. Furthermore, Johan and Hapsari (2020) assessed the impact of gender on Indonesian banking performance and discovered that diversity had a detrimental effect on banking performance.…”
Section: Empirical Reviewmentioning
confidence: 99%